Negotiating the screen: Indonesian audience reception of AI virtual characters and its implications for film marketing communication - Chatarina Heny Dwi Surwati; Eka Nada Shofa Alkhajar; Tanti Hermawati; Laurence Lingat Ramos (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2026)
This study examines how Indonesian film audiences receive virtual characters built with artificial intelligence (AI), and it asks what that reception implies for film marketing communication. Screen culture, in this article, refers to the shared viewing habits, tastes, and meaning-making practices through which audiences engage with moving images. The objectives are to map the patterns of audience reception, to explain how cultural background mediates the meaning audiences assign to virtual characters, and to translate those patterns into specific implications for marketing. Data were gathered through an online survey of 36 purposively selected respondents who are students, alumni, and practitioners in communication and film, so the design is exploratory rather than representative of the national audience. Analysis combined descriptive statistics with thematic coding of open-ended answers. The results reveal a consistent pattern of negotiated reception. Familiarity with computer-generated imagery is high, yet concern about losing acting authenticity (80.6%) and reducing actor employment (69.4%) remains pronounced, and most respondents accept virtual characters only for certain roles (77.8%). Audiences also prefer characters that look openly artificial (52.8%) over near-human ones, a preference that reads as a way of avoiding uncanny valley discomfort. Read through Hall's encoding and decoding model and Mori's uncanny valley, these findings extend reception theory to AI character reception in a non-Western screen culture, and they direct marketing toward genre-calibrated, transparency-led positioning rather than technology-centred promotion.